Ablation Index‐guided point‐by‐point ablation versus Grid annotation‐guided dragging for pulmonary vein isolation: A randomized controlled trial. (24th November 2021) - Mulder, Mark J.; Kemme, Michiel J. B.; Hopman, Luuk H. G. A.; Hagen, Amaya M. D.; van de Ven, Peter M.; Hauer, Herbert A.; Tahapary, Giovanni J. M.; van Rossum, Albert C.; Allaart, Cornelis P.
Abstract: Introduction: Radiofrequency (RF) atrial fibrillation (AF) ablation using a catheter dragging technique may shorten procedural duration and improve durability of pulmonary vein isolation (PVI) by creating uninterrupted linear ablation lesions. We compared a novel AF ablation approach guided by Grid annotation allowing for "drag lesions" with a standard point‐by‐point ablation approach in a single‐center randomized study. Methods: Eighty‐eight paroxysmal or persistent AF patients were randomized 1:1 to undergo RF‐PVI with either a catheter dragging ablation technique guided by Grid annotation or point‐by‐point ablation guided by Ablation Index (AI) annotation. In the Grid annotation arm, ablation was visualized using 1 mm³ grid points coloring red after meeting predefined stability and contact force criteria. In the AI annotation arm, ablation lesions were created in a point‐by‐point fashion with AI target values set at 380 and 500 for posterior/inferior and anterior/roof segments, respectively. Patients were followed up for 12 months after PVI using ECGs, 24‐h Holter monitoring and a mobile‐based one‐lead ECG device. Results: Procedure time was not different between the two randomization arms (Grid annotation 71 ± 19 min, AI annotation 72 ± 26 min, p  = .765). RF time was significantly longer in the Grid annotation arm compared with the AI annotation arm (49 ± 8 min vs. 37 ± 8 min, respectively, p  < .001). Atrial tachyarrhythmia recurrence was documented in 10 patients (23%) in the Grid annotation arm compared with 19 patients (42%) in the AI annotation arm with time to recurrence not reaching statistical significance ( p  = .074). Conclusions: This study shows that a Grid annotation‐guided dragging approach provides an alternative to point‐by‐point RF‐PVI using AI annotation.